Hadith #2573 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Nafi' bin Abi Nafi' نافع بن أبي نافع البزاز (Sunan Abi Dawud)
My foster-father said to me – he was one of Banu Murrah ibn Awf, and he was present in that battle, the battle of Mu’tah: By Allah, as if I am seeing Ja’far who jumped from his reddish horse and hamstrung it; he then fought with the people until he was killed. Abu Dawud said: The tradition is not strong.
Grade: Hasan